Transformasi Pembelajaran Akidah Akhlak Berbasis Game Based Learning Berbantuan Quizlet di Madrasah Ibtidaiyah - Diana, Alfi Elma; Maziyah, Nailatus Sa’adah; Zainiyati, Husniyatus Salamah; Asrohah, Hanun (Program Studi PGMI STAI Auliaurrasyidin Tembilahan, 2024)
Technological advances encourage the integration of technology in education in various schools, especially in learning Islamic Religious Education (PAI). The role of teachers becomes important in utilizing technology, one of which is through the Game-Based Learning (GBL) method. This method presents a fun and varied learning experience through game elements such as prizes, challenges and scores. This study aims to explore the use of GBL in PAI at MI Islamiyah Butoh by utilizing the Quizlet application. The study used a qualitative approach with interviews as the data collection method. The results showed that the Quizlet app, which allows students to access materials and quizzes, was effective in improving students' motivation and grades. In addition, the app provides an evaluation at the end of the lesson, so MI Islamiyah Butoh succeeded in making an innovative transformation in PAI learning in the digital era. The use of GBL is proven to make learning more effective, interesting and relevant.